The Efficacy of Ketogenic Diet in 60 Chinese Patients With Dravet Syndrome - Tian, Xiaojuan; Chen, Jiaoyang; Zhang, Jing; Yang, Xiaoling; Ji, Taoyun; Zhang, Yao; Wu, Ye; Fang, Fang; Wu, Xiru; Zhang, Yuehua (Frontiers in Neurology, 2019)
Objective: To evaluate the efficacy and safety of ketogenic diet (KD) in patients with Dravet syndrome (DS). Methods: 60 DS patients receiving treatment of KD for more than 12 weeks from 2009 to 2018 were analyzed retrospectively. Modified Johns Hopkins protocol was used to initiate KD. Seizure frequency，electroencephalogram (EEG)，cognition，language，and motor function of the patients were assessed. Side effects were monitored and adjusted accordingly. SPSS 23.0 software was used for all statistical analysis. Results: Totally 60 DS patients (34 boys, 26 girls) received treatment of KD more than 12 weeks，and among them 41 (68.3%) patients remained on the diet more than 24 weeks，22（36.7%）patients more than 48 weeks. Seizures in 35 patients (58.3%) were reduced over 50% at 12 weeks, and the KD effect was observed within 2 weeks in most of them. At 24 weeks, 61.1% (25/41) of the patients had a >50% seizure reduction. At 48 weeks, 77.3% (17/22) had an over 50% reduction in their seizure frequency. With the treatment of KD in the 60 DS patients, 10 patients had ever been seizure free for 12 months to 24 months (The median duration was 20 months). In 10 KD-effective patients, the background rhythm of their EEG showed obvious improvement，and interictal epileptic discharges decreased significantly. Cognitive function of 22 patients was improved. Language progressed in 14 patients. Motor function was improved in 13 patients. The efficacy of KD in DS patients did not correlate with the seizure onset age, the starting age of KD treatment, the SCN1A mutation and the numbers of antiepileptic drugs combined with KD treatment. The main adverse reactions of KD in the treatment process were gastrointestinal symptoms and metabolic disorders. Conclusions: KD treatment in DS patients has many advantages, including working rapidly, being effective in more than half of the DS patients and tolerable adverse reactions. Pharmoco-resistant DS patients are suggested to receive KD treatment.